PS-BPC04-3: LOWER NOCTURNAL SYSTOLIC BLOOD PRESSURE IS ASSOCIATED WITH CARDIOVASCULAR MORTALITY IN HEART FAILURE WITH REDUCED EJECTION FRACTION PATENTS. (January 2023) - Kim, Andrew T; Ito, Asahiro; Ito, Ayaka; Hayashi, Hiroya; Ogawa, Mana; Kitada, Ryoko; Ishikawa, Sera; Iwata, Shinichi; Izumiya, Yasuhiro; Fukuda, Daiju
Abstract : Objective: Blood pressure (BP) and its variability, especially nocturnal were associated with all-cause death and cardiovascular mortality in general population. However, little is known about the association between nocturnal BP variables (average value and variability) and cardiovascular mortality in patients with heart failure with reduced ejection fraction (HFrEF). Design and method: This study population consisted of 230 patients (mean age, 65 ± 13 years) who were admitted to our hospital due to HFrEF. Nocturnal BP was measured hourly using a home BP monitoring device, and its variability were expressed as the coefficient of variation of all readings. Results: During median follow-up period of 37 months, 19 (8%) patients had cardiovascular mortality. Compared with survivors, nocturnal systolic BP was significantly lower in cardiovascular mortality patients (125 ± 24 mmHg vs 110 ± 17 mmHg, p = 0.007). Univariate analysis showed that age, chronic kidney disease, nocturnal systolic and diastolic BP were associated with cardiovascular mortality. Cox proportional hazards models showed that nocturnal systolic BP was associated with cardiovascular mortality after adjustment for age and CKD (odds ratio: 0.97; 95% confidence interval: 0.94–0.99; P = 0.01), whereas nighttime diastolic BP and their variables (average value and variability) were not. Similarly, nocturnal systolic BP < 108 mmHg was predictive of cardiovascular mortality (odds ratio: 3.84; 95% confidence interval: 1.53–9.67; P = 0.004), Conclusion: Lower nocturnal systolic BP was associated with cardiovascular mortality in patients with HFrEF. Intervention for nocturnal systolic BP could avoid cardiovascular events and consequently reduce the risk of cardiovascular mortality.